Sociodemographic factors associated with consumption of confectionery among obese and non-obese adults: a secondary analysis - Cheah, Yong Kang; Azahadi, Mohd; Mohamad Nor, Noor Safiza; Phang, Siew Nooi; Abd Manaf, Noor Hazilah (Elsevier, 2020)
The objective of the present study is to examine sociodemographic factors associated with consumption of confectionery among obese and non-obese adults in Malaysia. Secondary analysis of the Malaysian Adult Nutrition Survey (MANS) 2014 was performed. The survey was conducted in urban and rural areas in the 14 states of Malaysia, including the Federal Territory of Kuala Lumpur. Adults aged 18 years and above (n = 2696) were interviewed. The dependent variable was the total servings of confectionery consumed per week. An ordered logistic regression model was used to examine the associated sociodemographic factors in the decision of people to consume 0, 1−2, 3−5 and ≥6 servings of confectionery. Marginal effects of sociodemographic variables on confectionery consumption were calculated. Analyses stratified by bodyweight group were conducted. The results showed that income, education, gender, ethnicity, and employment status were significantly associated with consumption of confectionery. In particular, income, education, gender, ethnicity and employment status affected confectionery consumption, but not the other way around. However, no relationship was evidenced between age, marital status, household location and confectionery consumption. In conclusion, sociodemographic factors were related to consumption of confectionery. Policies aimed at discouraging consumption of confectionery should focus primarily on high income earners, well-educated individuals and Bumiputra